Impact! : the Threat of Comets and Asteroids. - Verschuur, Gerrit L. (Oxford University Press, 1997)
Most scientists now agree that some sixty-five million years ago, an immense comet slammed into the Yucatan, detonating a blast twenty million times more powerful than the largest hydrogen bomb, punching a hole ten miles deep in the earth. Trillions of tons of rock were vaporized and launched into the atmosphere. For a thousand miles in all directions, vegetation burst into flames. There were tremendous blast waves, searing winds, showers of molten matter from the sky, earthquakes, and a terrible darkness that cut out sunlight for a year, enveloping the planet in freezing cold. Thousands of sp.